(untitled) (Global Journal of Science Frontier Research, 2022)
Between August 2019 and October 2020, an ethnobotanical research was carried out to look at how the inhabitants of Nabiganj Upazila of Bangladesh’s Habiganj district was noted. The information regarding the ethnobotanical data was obtained by interviewing residents of different age groups, most of them were in the 15 to 55 age range, including medicinal herbalists and hakims. The present paper reported that 68 medicinal plants belonging to 41 families, and 60 genera which have been proven to be helpful in the treatment of 78 diseases. Out of these plant species, 24 belonged to herbs, 27 trees, eight shrubs, and nine climbers. However, other parts of medicinal plants, including the stem, bark, latex, leaf bud, pulp, petiole, fruits, and rhizome, Seed, root, calyx, and peduncle were also shown to be helpful. For each species, scientific name, local name, habit, family, ailments to be treated, mode of treatment, and part(s) used are provided.Local residents of gathered data on medicinal plants, including Nabiganj Upazila of Habiganj district.